Sistem Informasi Potensi Sumber Daya Alam (SDA) Desa Provinsi Kepulauan Riau - Hetty Cahyatie (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2019)
Natural Resource Potential Information System in Riau Islands Province is a Web-based information system where the application is built interactively using flash animation to make it easier for users to understand and understand easily. This application provides general information about the village's potential and is also displayed in graphical information making it easier for villages that have more potential. The goal to be achieved by the Natural Resource Potential Information System of Riau Islands Province is to become an integrated and sustainable organizer of the village and kelurahan data center in Riau Islands. Users of the Natural Resource Potential Information System of the Riau Islands Province who are registered starting from the village level up to the Regency level, so that in the present and future the system can function as a means to gather accurate and up-to-date data and information about villages and villages. This research uses a method using several approaches of application design with the waterfall method and blacbox and whitebox testing. The result of the research is a web-flash Village-based Natural Resource Potential Information System. The application built displays data by involving a variety of animations by prioritizing content characteristic from each region on the icon of each village. The Village Natural Resources Potential Information System also displays information comparisons from villages in Bintan District.